DEVELOPMENT OF MULTIMEDIA INTERACTIVE LEARNING SIMULATION MODEL TO ENHANCE STUDENT MOTIVATION IN ICT SUBJECT - Dinda Agus Triyana, - (2011)
This research that entitled with "Development of Multimedia Interactive Learning Simulation Model To Enhance Student Motivation in ICT Subject" is a research and development with a purpose to develop ansimulation model as interactive multimedia for learning that can increasestudent motivation of learning. This research is also have purposes to discoverstudent opinion and interest toward learning that use multimedia simulation model, to see validity or feasibility of simulation model multimedia that hasbeen developed and also to see student appraisal toward multimedia that has beendeveloped. From phases of research and development that has been done,obtained research data from questionnaires that are: field survey questionnairethat has been given to 39 students of class VII in Vijaya Kusuma Yunior High School of Bandung inanalysis phase, expert validation questionnaires in development phase that hasbeen given to lecturers and teachers of ICT, student appraisal toward multimediaquestionnaires andstudent motivation of learning questionnaires inimplementation phase. From this research, obtained some results that are: 1)almost all student give positive responses toward learning that use multimediasimulation model, 2) simulation model multimedia that has been developed isvery good-rated and proper to use with average percentage of feasibility as big as 84.60% by media experts and 92.25% by subject of instruction experts, 3) studentappraised by very good-rated toward simulation model multimedia that hasbeen developed with appraisal percentage as big as 80.00%, 4) there is anincrease as big as 6.89% from student motivation of learning questionnairebetween before and after using of simulation model multimedia.